The value of FDG-PET/CT metabolic parameters and treatment metabolic response in predicting long-term survival of patients with diffuse large B-cell lymphoma - Abbas Yousefikoma; Mohamad Mehdi Karimy Taha (Novelty in Biomedicine)
Background: Few trials have been conducted regarding using PET/CT metabolic parameters as a predictor for the long-term survival of patients with lymphoma. The present study aimed to determine the prognostic value of quantitative metabolic parameters based on FDG-PET/CT in predicting 2-year mortality and disease recurrence in patients with diffuse large B-cell lymphoma (DLBCL).